Synthesis, Physicochemical Analysis, and Characterisation of Periwinkle-Based Chitosan - Peter, Ijwo Omirenyi; Kyenge, B. A (Journal of Discoveries in Applied and Natural Science, 2026)
The growing accumulation of shell waste from aquatic food processing presents an environmental challenge and an opportunity for sustainable biopolymer production. This study reports the extraction, physicochemical analysis, and characterisation of chitosan derived from periwinkle shell waste as a locally sourced alternative to conventional crustacean-based chitosan. Chitin was isolated through sequential demineralisation, deproteinisation, and decolourisation, followed by alkaline deacetylation to obtain chitosan. The resulting material was analysed using Fourier Transform Infrared Spectroscopy (FTIR), X-ray Powder Diffraction (XRD), Scanning Electron Microscopy (SEM), and Energy-Dispersive X-ray Spectroscopy (EDX). The extracted chitosan exhibited a high degree of deacetylation (86%), confirming effective conversion from chitin. Physicochemical evaluation revealed low moisture and protein contents (0.5% and 0.4%), indicating good stability, while moderate ash content (5.6%) suggested partial residual mineral presence. FTIR confirmed characteristic functional groups of chitosan, XRD revealed enhanced crystallinity relative to native chitosan, and SEM showed a rough, porous morphology with high surface area. EDX analysis indicated residual calcium from the shell matrix. However, periwinkle shell waste represents a viable and sustainable source of functional chitosan suitable for food, agricultural, environmental, and biomedical applications.